Formation of upland rice drought-tolerant mutants by mutation induction and in vitro selection - Rossa Yunita; ISWARI S. DEWI; ENDANG GATI LESTARI; RAGAPADMI PURNAMANENGSIH; SUCI RAHAYU; MASTUR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yunita R, Dewi IS, Lestari EG, Purnamanengsih R, Rahayu S, Mastur. 2020. Formation of upland rice drought-tolerant mutants by mutation induction and in vitro selection. Biodiversitas 21: 1476-1482. Increased production can be done by increasing the planting area, but the available land is sub-optimal land with drought stress. Drought-tolerant rice varieties are needed to utilize this land. To create drought-tolerant rice can use induction mutation and in vitro selection methods. This study aims to obtain tolerant upland rice mutants through mutation and in vitro selection. The parents used were Batutegi and Situpatenggang varieties. This research consisted of several main activities, namely callus induction, determination of LD 50% value ofPEG determination of LC 50% value of gamma-ray irradiation, mutation induction and in vitro selection, bud regeneration and acclimatization. The results of this study are mutant callus formed by gamma-ray irradiation at a dose of 24.68 Gy for Situpatenggang and 22.15 Gy for Batutegi (LD50) and selected on PEG media at a dose of 24.11% for Situpatenggang and 25.18% for Batutegi (LC50). The mutant callus regenerated on MS + BA 3 mg/L + Zeatin 0.1 mg/L produced 83 Situpatenggang shoots and 73 Batutegi shoots and successfully acclimatized were 52 Situpatenggang lines and 49 Batuteg linesBatutegi